The Limits of Artificial Intelligence in Judicial Reasoning: Jurisprudential Analysis of Islamic Legal Authority - Panji Anugrah; Ahmad Rizky Ilyas; Kurniati; Zulhas’ari Mustafa (Sunan Kalijaga State Islamic University Yogyakarta, Indonesia., 2025)
The development of Artificial Intelligence (AI) in judicial systems has raised debates regarding its limitations in judicial reasoning, particularly within the Religious Courts. Previous studies have generally examined AI from technological and administrative perspectives, while Islamic legal studies have focused more on judicial reasoning and ijtihad. However, limited research has integrated AI with the perspective of the four madhhabs in judicial reasoning. This study aims to analyze the legitimacy, limitations, and position of AI in the legal reasoning of Religious Court judges based on positive law and the perspectives of the four Islamic schools of thought. This research employs a qualitative method with a normative juridical approach through library research and document analysis of Supreme Court regulations, court decisions, classical fiqh literature, and scholarly articles related to AI and law. The findings indicate that AI may function as a supporting tool for legal data retrieval and analysis but cannot replace judges’ authority in making legal decisions. The four madhhabs consistently position humans as the primary subjects of legal determination due to their scholarly competence, moral judgment, and religious responsibility. These findings contribute to the development of legal technology studies by integrating Islamic jurisprudence perspectives into contemporary debates on AI governance in modern judicial systems.